PERLINDUNGAN HUKUM TERHADAP KONSUMEN PROPERTI SISTEM PRE PROJECT SELLING BERDASARKAN PRINSIP PERLINDUNGAN KONSUMEN DALAM UU NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Rimbawa, I Made Artha (VYAVAHARA DUTA, 2021)
Pre-Project Selling is an agreement made by the parties to the sale and purchase of property before the project is built and the new one is sold in the form of pictures or concepts. The reason developers develop this Pre-Project Selling practice is to find out the market’s response to the property product that will be built (test the water). The Pre-Project Selling practice is a special agreement. This is because the object of the agreement is an image or concept from the developer. The rise of the Pre-Project Selling certainly presents some problems. One of them is about protecting consumers from images or concepts proposed by Developers. In this study will discuss the Consumer protection of Consumer Protection against Pre-Project Selling practices that refer to the legal principles in the Consumer Protection Act. This type of research is normative research, which is research based on studies that are in accordance with the theories and legal rules that have been determined. This normative research also functions to provide a juridical argument against the occurrence of emptiness, obscurity, and norm conflicts. Thus this research is considered very important as a policy input material in order to provide the value of justice for the community.